Influence of Different Pulse Length towards Motility and Viability of Ornamental Japanese Carp (Cyprinus carpio Var. Koi) Sperm through Electroporation Method - Aisyah, Diana; Soeprijanto, Agoes; Kilawati, Yuni (The Journal of Experimental Life Science, 2017)
Successful studies about implementation of electroporation method which sperm becomes gene transfer medium for fish transgenesis have reported. Motility and viability are two major factors in successful of electroporation. The objective of the study was to determine optimal pulse length of electroporation towards the motility and viability of Koi fish sperm. The study was conducted at the Central Laboratory of Biological Sciences and Reproduction of Brawijaya University. The data analysis was conducted using completely randomized design. The electroporation method was carried out using voltage of 30 volt with pulse number of 4 times. The pulse length of the electroporation (based on treatment) was 0.5, 1 and 1.5 ms. The result showed the highest percentage of motility was 3.67% in treatment A (pulse length 0.5 ms) with coefficient correlation R2 = 0.9643 and the best percentage of viability was 79.67% in treatment A (pulse length 0.5 ms) with coefficient correlation R2 = 1. Correlation between the pulse length treatment (electroporation) toward motility and viability of Koi fish sperm, in which longer duration of pulse length treatment (electroporation) would decrease the motility and viability percentage of the fish sperm.Keywords: Electroporation, Motility, Pulse length, Sperm, Viability.